2017
DOI: 10.1021/acs.jpcc.7b02602
|View full text |Cite
|
Sign up to set email alerts
|

Importance of ZIF-90 Lattice Flexibility on Diffusion, Permeation, and Lattice Structure for an adsorbed H2/CH4 Gas Mixture: A Re-Examination by Gibbs Ensemble Monte Carlo and Molecular Dynamics Simulations

Abstract: Adsorption and diffusion of the gas mixture H2/CH4 in the metal–organic framework (MOF) of structure type zeolitic imidazolate framework-90 (ZIF-90) are revisited. While the adsorption can successfully be examined in Gibbs ensemble Monte Carlo (GEMC) simulations using the common approximation of a rigid lattice, the dynamics of methane in ZIF-90 is remarkably influenced by the lattice flexibility. Molecular dynamics (MD) simulations not only show a strong influence of the lattice flexibility on the diffusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…3.3.2 Window exibility. Previous works 8,21,77 have shown that degrees of freedom associated with the MOF structure and their coupling with diffusing molecules can in some cases be vital to accurate description of molecular diffusion. To probe these effects, the time-averaged diameters of the empty and adsorbate-loaded windows for each MOF were calculated.…”
Section: Inuence Of Mof Pore Propertiesmentioning
confidence: 99%
“…3.3.2 Window exibility. Previous works 8,21,77 have shown that degrees of freedom associated with the MOF structure and their coupling with diffusing molecules can in some cases be vital to accurate description of molecular diffusion. To probe these effects, the time-averaged diameters of the empty and adsorbate-loaded windows for each MOF were calculated.…”
Section: Inuence Of Mof Pore Propertiesmentioning
confidence: 99%
“…Most of the MOFs seem to host the molecules, larger than the crystallographically analyzed pore aperture, which is the main reason of lattice flexibility in these MOFs. The lattice flexibility has been observed for different MOF structures including but is not limited to ZIF‐7, 72,73 ZIF‐8, 74 ZIF‐90, 75 and MIL‐ 53 76 . Many research group have explored intensively and investigated the phenomenon of lattice flexibility by using different characterization approaches and came to the similar conclusion mentioned above.…”
Section: Engineering Directionsmentioning
confidence: 70%
“…Apart from these, fumed silica, which is non-porous material is used throughout the world in MMM preparation. In terms of fillers choice criteria for MMM preparation, most particles have been chosen based on their gas sorption behavior rather than their transport behavior of gaseous molecules and this principle has been different MOF structures including but is not limited to ZIF-7, 72,73 ZIF-8, 74 ZIF-90, 75 and MIL-53. 76 Many research group have explored intensively and investigated the phenomenon of lattice flexibility by using different characterization approaches and came to the similar conclusion mentioned above.…”
Section: Role Of Particles and Lattice Flexibilitymentioning
confidence: 99%
“…The dependence of diffusivity to temperature can be explained by higher thermal energy of particles at higher temperatures in the Arrhenius theory. The diffusion coefficient of gas is also dependent on the thermal velocity of molecules and the size and shape of the cages 43.…”
Section: Resultsmentioning
confidence: 99%